Unusual Cage Rearrangements in 10-Vertex nido-5,6-Dicarbaborane Derivatives: An Interplay between Theory and Experiment - Štíbr, Bohumil; Holub, Josef; Bakardjiev, Mario; Lane, Paul D; McKee, Michael L; Wann, Derek A; Hnyk, Drahomír (Inorganic chemistry, 2017)
The reaction between selected X-nido-5,6-C2B8H11 compounds (where X = Cl, Br, I) and "Proton Sponge" [PS; 1,8-bis(dimethylamino)naphthalene], followed by acidification, results in extensive rearrangement of all cage vertices. Specifically, deprotonation of 7-X-5,6-C2B8H11 compounds with one equivalent of PS in hexane or CH2Cl2 at ambient temperature led to a 7 → 10 halogen rearrangement, forming a series of PSH+[10-X-5,6-C2B8H10]- salts. Reprotonation using concentrated H2SO4 in CH2Cl2 generates a series of neutral carbaboranes 10-X-5,6-C2B8H11, with the overall 7 → 10 conversion being 75%, 95%, and 100% for X = Cl, Br, and I, respectively. Under similar conditions, 4-Cl-5,6-C2B8H11 gave ∼66% conversion to 3-Cl-5,6-C2B8H11. Since these rearrangements could not be rationalized using the B-vertex swing mechanism, new cage rearrangement mechanisms, which are substantiated using DFT calculations, have been proposed. Experimental 11B NMR chemical shifts are well reproduced by the computations; as expected δ(11B) for B(10) atoms in derivatives with X = Br and I are heavily affected by spin-orbit coupling.